Systematic review and meta-analysis of hepatic resection versus transarterial chemoembolization for solitary large hepatocellular carcinoma. Issue 8 (August 2017) - Stevens, Claire L.; Awad, Andrew; Abbas, Saleh M.; Watters, David A.K.
Abstract: Background: Surgical techniques and pre-operative patient evaluation have improved since the initial development of the Barcelona clinic liver cancer staging system. The optimal treatment for solitary hepatocellular carcinoma ≥5 cm remains unclear. The aim of this study was to review the long-term survival outcomes of hepatic resection versus transarterial chemoembolisation (TACE) for solitary large tumours. Methods: EMBASE, MEDLINE, Pubmed and the Cochrane database were searched for studies comparing resection with TACE for solitary HCC ≥5 cm. The primary outcome was overall survival at 1, 3 and 5 years. Results: The meta-analysis combined the results of four cohort studies including 861 patients where 452 underwent hepatic resection and 409 were treated with TACE to an absence of viable tumour. The pooled HR for 3 year OS rate calculated using the random effects model was 0.60 (95% CI 0.46–0.79, p < 0.001; I 2 = 54%, P = 0.087). The pooled HR for 5 year OS rate calculated using the random effects model was 0.59 (95% CI 0.43–0.81, p = 0.001; I 2 = 80%, P = 0.002). Conclusion: Hepatic resection has been shown to result in greater survivability and time to disease progression than TACE for solitary HCC ≥5 cm. Where a patient is fit for surgery, has adequate liver function and a favourable tumour, resection should be considered.